Timor-Leste Economic Report, April 2020 : A Nation Under Pressure - World Bank Group (World Bank, Washington, DC, 2020)
Economic activity is expected to contract in 2020, owing to political uncertainty and the impact of the novel coronavirus (COVID-19). Despite a return to economic growth in 2019, failure to approve a state budget for 2020, renewed political uncertainty, and the global COVID-19 outbreak have all considerably weighed down prospects for 2020. In addition, recent heavy rains caused floods that affected thousands of people and many businesses. Given these mutually reinforcing negative effects, the GDP growth forecast for 2020 has been lowered from 4.6 percent (as projected in the October 2019 report) to -4.8 percent. However, this projection is still subject to much uncertainty. In particular, the economic impacts of COVID-19 will largely depend on the direct impact of the virus, the scope and duration of the public health measures adopted, as well as the economic policy response. The Special Focus discusses some of the economic transmission channels and puts forward a set of policy interventions that may help cushion the impact on businesses and people’s livelihoods.